Coexistence of thrombotic thrombocytopenic purpura and immune thrombocytopenic purpura in an Asian woman: a case report - Hangping Ge; Zhan Shi; Zhiyin Zheng; Qiuping Zhu; Lili Hong; Yu Zhang; Jianping Shen; Shu Deng (Journal of International Medical Research, 2022)
A 33-year-old Chinese woman with a history of immune thrombocytopenic purpura presented with heavy menstrual bleeding. She was found to have thrombocytopenia, plasma ADAMTS13 activity of 0%, and positivity for the plasma ADAMTS13 inhibitor. She was diagnosed with the coexistence of thrombotic thrombocytopenic purpura and immune thrombocytopenic purpura. The patient was treated by plasmapheresis, a glucocorticoid, and rituximab. Her platelet level returned to normal, and she was discharged 28 days after admission. The number of plasmapheresis sessions and the timing of rituximab administration may be the key aspects of management of patients with thrombotic thrombocytopenic purpura who have underlying immune dysfunction caused by diseases such as immune thrombocytopenic purpura.